Diverse flower-visiting responses among pollinators to multiple weather variables in buckwheat pollination - Tadashi Miyashita; Shouta Hayashi; Kae Natsume; Hisatomo Taki (Scientific Reports, 2023)
Abstract Response diversity to environmental change among species is important for the maintenance of ecosystem services, but response diversity to changes in multiple environmental parameters is largely unexplored. Here, we examined how insect visitations to buckwheat flowers differ among species groups in response to changes in multiple weather variables and landscape structures. We found differences in responses to changes in weather conditions among insect taxonomic groups visiting buckwheat flowers. Beetles, butterflies, and wasps were more active in sunny and/or high-temperature conditions, whereas ants and non-syrphid flies showed the opposite pattern. When looking closely, the different response pattern among insect groups was itself shown to be different from one weather variable to another. For instance, large insects were responsive to temperatures more than small insects while smaller insects were responsive to sunshine duration more than large insects. Furthermore, responses to weather conditions differed between large and small insects, which agreed with the expectation that optimal temperature for insect activity depends on body size. Responses to spatial variables also differed; large insects were more abundant in fields with surrounding forests and mosaic habitats, whereas small insects were not. We suggest that response diversity at multiple spatial and temporal niche dimensions should be a focus of future studies of the biodiversity–ecosystem service relationships.